Perbaikan Sudut Daun Populasi Komposit Tanaman Jagung Melalui Hibridisasi Dengan Varietas Hibrida - I Wayan Sudika; Dwi Ratna Anugrahwati (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
This study aims to determine the average leaf angle, harvest age and yield of F1 from cross-hybrid composite; heterosis value and knowing the maternal effect of these three traits on maize. The experiment was carried out in technically irrigated rice fields from November 2019 to February 2020. The design used in this experiment was a randomized block design with two replications. The treatment was 28 F1 as a result of crossing P8IS vs NK212 and P8IS vs NK7328 and their respective reciprocal crosses. The experimental data were analyzed by means of analysis of variance and further tested with the LSD test at the 5 percent level. Heterosis values were calculated on the basis of the parents whose scores were higher (High Parent Heterosis). The t test at the 5% level was used to determine whether the maternal effect was significant. The results showed that the mean leaf angles of F1 lines from crosses and reciprocal P8IS vs NK212 were the same as the two parents; whereas the P8IS vs NK7328 cross is different. The reciprocal of cross number 13 (P8IS vs Nk7328 /R13) has smaller leaf angle than P8IS and is the same as the leaf angle of NK7328. The yield of the F1 lines from the two types of crosses was the same as each of the two parents; however, there was a tendency for an increase in yield compared to P8IS for most of the F1 lines. There was a change in leaf angle properties, harvest age and yield of F1 lines compared to one of the best parents with heterosis values are negative and positive with variations from 0.00 to 65.70 percent. Coefficient of correlation between heterosis with the average value of traits was classified as strong for the harvest age; moderate for yield and weak for leaf angle. These three traits in the two types of crosses showed no maternal effects. Smaller leaf angle, super early harvest age and higher yield, are possible to be obtained from the lines of both crosses.